Positive, Proactive, and Committed: The Surprising Connection Between Good Citizens and Expressed (vs. Suppressed) Anger at Work. (November 2014) - Stickney, Lisa T.; Geddes, Deanna
Abstract In two studies, we examine the relationship of positive and negative trait affectivity (PA/NA), organizational commitment, and emotional exhaustion with organizational member anger. Utilizing the dual threshold model (DTM) constructs of expressed and suppressed anger (Geddes & Callister, 2007), we find employees with high organizational commitment express anger to relevant others, that is, to management or to those responsible for the anger‐provoking situation. In contrast, emotionally exhausted employees and those with high NA tend to suppress their anger, venting only to uninvolved parties or remaining silent. Findings also indicate a positive relationship with PA and anger expression—a connection rarely considered or examined in anger research. Further, expressed anger was predictive of perceived improvement with problematic situations, while suppressed anger forms led to perceptions that the situation at work deteriorated.